2001
DOI: 10.1161/hq0801.093505
|View full text |Cite
|
Sign up to set email alerts
|

Do Total and High Density Lipoprotein Cholesterol and Triglycerides Act Independently in the Prediction of Ischemic Heart Disease?

Abstract: Abstract-Several studies have suggested that men with raised plasma triglycerides (TGs) in combination with adverse levels of other lipids may be at special risk of subsequent ischemic heart disease (IHD). We examined the independent and combined effects of plasma lipids at 10 years of follow-up. We measured fasting TGs, total cholesterol (TC), and high density lipoprotein cholesterol (HDLC) in 4362 men (aged 45 to 63 years) from 2 study populations and reexamined them at intervals during a 10-year follow-up. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 32 publications
1
54
0
3
Order By: Relevance
“…The mean value for total cholesterol in our sample was similar to fasting mean levels in the Dietary and Nutritional Survey of British Adults 50 and those in the Caerphilly study. 51 This is the first large birth cohort study to our knowledge to consider the association between birth weight and lipids in older adults. Our unadjusted estimate combined for both sexes is similar to that found in a recent meta-analysis of the association between birth weight and total cholesterol in which an increase in 1 kg of birth weight was associated with a 0.05-mmol/L reduction in total cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…The mean value for total cholesterol in our sample was similar to fasting mean levels in the Dietary and Nutritional Survey of British Adults 50 and those in the Caerphilly study. 51 This is the first large birth cohort study to our knowledge to consider the association between birth weight and lipids in older adults. Our unadjusted estimate combined for both sexes is similar to that found in a recent meta-analysis of the association between birth weight and total cholesterol in which an increase in 1 kg of birth weight was associated with a 0.05-mmol/L reduction in total cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…The men were seen first in 1979-1983 and they have subsequently been seen at 5-y intervals, that is they have been followed for 20-24 y. Details of the methods and reports on prediction of vascular disease by platelet, haemostatic, rheological, lipid and psychosocial factors have been reported elsewhere (Gallacher et al, 1999;Elwood et al, 2001a, b;Baker et al, 2002;Yarnell et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Evidence on prevalent vascular disease, ischaemic heart disease and/or stroke, including a 12-lead ECG, was recorded. Samples of fasting blood were taken for estimation of platelet (Elwood et al, 2001a), haemostatic (Baker et al, 2002), rheological (Elwood et al, 2001b), lipids (Yarnell et al, 2001), psychosocial (Gallacher et al, 1999) and other factors of possible relevance to vascular disease.…”
Section: Methodsmentioning
confidence: 99%
“…11 Triglycerides were also associated with CHD risk in the Caerphilly Heart Disease Study (CHDS), again independent of total cholesterol and HDL-cholesterol levels. 12 At the same time, no prospective, controlled trials have demonstrated the benefits of triglyceride lowering alone on clinical or cardiovascular outcomes, perhaps because available triglyceride-lowering agents also affect other lipid and lipoprotein concentrations. Although the PROCAM scoring scheme includes triglycerides as a major independent risk factor, the NCEP ATP III guidelines do not.…”
Section: Iii-16 Circulation June 15 2004mentioning
confidence: 99%